PERAN LINGKUNGAN KELUARGA TERHADAP HASIL BELAJAR MATEMATIKA PADA SISWA KELAS VI SD GMIT KUANINO 1 - Rovi Satra Paulus; Chintia M.P Ati; Roswita Lioba Nahak (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The Role of the Family Environment on Mathematics Learning Outcomes of Sixth Grade Students at SD GMIT Kuanino 1. Thesis, Elementary School Teacher Education Program, Universitas Citra Bangsa Kupang. This study aims to analyze the factors that hinder low mathematics learning outcomes among elementary school students, particularly sixth grade students at SD GMIT Kuanino 1, in terms of internal and external factors, as well as to identify the role of the family environment in students’ mathematics learning outcomes. This research employed a qualitative approach with a descriptive research design. The research subjects consisted of the classroom teacher, sixth grade students, and parents, while the object of the study was the role of the family environment in mathematics learning outcomes of elementary school students. Data were collected through observation, interviews, and documentation. The collected data were then analyzed through data reduction, data presentation, and conclusion drawing to obtain a clear and in-depth description of the conditions of mathematics learning in elementary schools. The results of the study indicate that low mathematics learning outcomes are influenced by internal and external factors. Internal factors include low concentration and student activeness, lack of learning motivation and interest, low self-confidence, and suboptimal learning discipline. External factors include monotonous teaching methods, high levels of task difficulty, unconducive classroom atmosphere, limited learning facilities, lack of parental assistance and motivation, and weak collaboration between schools and families. The role of the family environment in improving mathematics learning outcomes of elementary school students is manifested through providing motivation and appreciation, supplying adequate learning facilities, assisting and supervising learning activities at home, monitoring discipline and managing study time, and maintaining sustainable cooperation with the school. The conclusion of this study shows that the family environment plays a very important role in supporting students’ mathematics learning outcomes. Optimal family support is able to increase students’ learning motivation and academic achievement, while a lack of family involvement results in low motivation and mathematics learning outcomes.